Anomalous venoatrial connections – CT and MRI assessment - Antonio Celona; Elio Caruso; Silvia Farruggio; Lilia Oreto; Maria Cristina Inserra; Maria Teresa Cannizzaro; Tommaso D'Angelo; Silvio Mazziotti; David Angel Ortiz; Davide Calvaruso; Christian Booz; Salvatore Agati; et al. (Heliyon, 2023)
Abnormal venous atrial (VA) connections present a congenital heart disease (CHD) challenge for pediatric cardiologists. Fully anatomical evaluation is very difficult in prenatal and perinatal follow-up, but it has a profound impact on surgical correction and outcome. The echocardiogram is first-line imaging and represents the gold standard tool for simple abnormal VA connection. CT and MRI are mandatory for more complex heart disease and “nightmare cases”. 3D post-processing of volumetric CT and MRI acquisition helps to clarify anatomical relationships and allows for the creation of 3D printing models that can become crucial in customizing surgical strategy.Our article describes a ten-year (2013–2022) tertiary referral CHD center of abnormal AV connections investigated with CT and MRI, illustrating most of these complex diseases with the help of volume rendering (VR) or multiplanar reconstructions (MPR). The nightmarish cases will also be addressed due to the complex cardiovascular arrangement that requires a challenging surgical solution for correction along with the post-surgical complications.